2022
DOI: 10.1155/2022/1189613
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Application of Traditional Chinese Auspicious Images in Environmental Art Design Based on VR Senses

Abstract: Virtual reality is high-tech involving multiple disciplines developed at the end of the 20th century. Virtual reality technology can be used in many fields, such as remote control, business, education, entertainment, visual simulation, military, art, architecture, and network. Essentially, virtual reality technology has three basic characteristics: immersion, interaction, and imagination. This study analyzes the advantages of VR technology in the specific application of environmental art design based on case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%